The Road to FAIR Energy Data: Motivations, Shortcomings, and Use Cases - Awadallah, Rawia; Tammaro, Anna Maria (The International information & library review, 2025)
The transition to sustainable energy relies on effective data management, yet significant gaps persist in the implementation of FAIR (Findable, Accessible, Interoperable, and Reusable) data principles, particularly in the solar energy sector. A lack of standardization, fragmented datasets, and limited accessibility hinder research progress, policy development, and technological innovation. This article explores the motivations driving researchers to address these challenges and examines the key barriers they encounter. Finally, we propose solutions to improve data sharing, enhance research collaboration, and promote sustainability through better data governance and interoperability. Strengthening FAIR data practices is essential for maximizing the impact of solar energy research and supporting the global shift toward renewable energy solutions.